Relevansi Nilai-nilai Islam dalam Tradisi Maddoja Bine terhadap Pendidikan Abad 21 - Nurasia; Muzakkir; Syamsuddin (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2024)
The public's belief in a tradition is of course inseparable from the many opinions of the outside community who are of the opinion that the traditions that are still preserved to this day deviate from the teachings of Islam and still contain animism, without clearly knowing what the meaning is and how to implement these traditions as stated in implementation of the Maddoja bine tradition which is the topic of research, the relevance of Islamic values in the Maddoja bine tradition to 21st century education is indeed very important to be studied further and primarily to maintain the existence of the Maddoja bine culture which contains important meanings for the Bugis people in order to ensure sustainability. , as information obtained through interviews using descriptive qualitative research methods, namely 1) the implementation of the Maddoja bine tradition is carried out for two to three days carried out in mutual cooperation, 2) Islamic values in the Maddoja bine tradition consist of aqidah values, sharia values and moral values 3) the relevance of Islamic values in the Maddoja bine tradition to education in the 21st century.